Disease Progression/Clinical Outcome Model for Castration‐Resistant Prostate Cancer in Patients Treated With Eribulin. (30th June 2015) - van Hasselt, JGC; Gupta, A; Hussein, Z; Beijnen, JH; Schellens, JHM; Huitema, ADR
<x xml:space="preserve">Abstract</x> Frameworks that associate cancer dynamic disease progression models with parametric survival models for clinical outcome have recently been proposed to support decision making in early clinical development. Here we developed such a disease progression clinical outcome model for castration‐resistant prostate cancer (CRPC) using historical phase II data of the anticancer agent eribulin. Disease progression was captured using the dynamics of prostate‐specific antigen (PSA). For clinical outcome, overall survival (OS) was used. The model for PSA dynamics comprised parameters for baseline PSA (23.2 ng/ml, relative standard error (RSE) 16.5%), growth rate (0.00879 day−1, RSE 12.6%), drug effect (0.241 µg·h·l−1 day−1, RSE 32.6%), and resistance development (0.0113 day−1, RSE 44.3%). OS was modeled according to a Weibull distribution. Predictors for survival included model‐predicted PSA time to nadir (TTN), PSA growth rate, Eastern Cooperative Oncology Group (ECOG) score, and baseline PSA. The developed framework can be considered to support informative design and analysis of drugs developed for CRPC.